Investigating the effect of heteroatom substitution in 2, 1, 3-benzoxadiazole and 2, 1, 3-benzothiadiazole compounds for organic photovoltaics. Issue 14 (22nd December 2017) - Cameron, Joseph; Abed, Mahmoud Matar; Chapman, Steven J.; Findlay, Neil J.; Skabara, Peter J.; Horton, Peter N.; Coles, Simon J.
Abstract : Subtle changes in the choice of the chalcogen atom in benzochalcogenadiazole 'small molecules' can lead to a marked difference in the PCE of bulk heterojunction organic solar cells. Abstract : Two new donor–acceptor−donor molecules, featuring either 2, 1, 3-benzothiadiazole (BT) or 2, 1, 3-benzoxadiazole (BO) and capped by benzofuranyl-thienyl groups, are presented. The structures of these novel compounds differ only in the identity of one heteroatom in the acceptor unit. Replacement of the sulfur atom in BT with oxygen results in a marked improvement in the performance of PC61 BM blends in bulk heterojunction organic photovoltaic (BHJ OPV) devices: a 10-fold increase in PCE is observed when switching to the BO analogue. This is partly due to a preferable morphology in the donor-fullerene blends formed upon spin-coating from chlorinated solvents.